Theodicy of culture and the Jewish ethos : David Koigen's contribution to the sociology of religion - Urban, Martina (Berlin ; Boston : Walter de Gruyter, 2012)
This volume presents the theory of culture of the Russian-born German Jewish social philosopher David Koigen (1879-1933). Heir to Hermann Cohen's neo-Kantian interpretation of Judaism as a religion of reason, he draws upon philosophical anthropology and the sociology of religion to go beyond Kantian formalism. The resulting primacy given to religious consciousness brought him close to Martin Buber, with whom he shared an interest in East European Hasidism as a source of religious renewal. Author of Ideen zur Philosophie der Kultur (1910) and Der moralische Gott (1922), among other works, Koige.
Theodicy of culture and the theory of the cultural act -- Beyond the a priori: toward a religion of intimacy -- Resituating Judaism: on pragmatism and phenomenology -- Ethos: a non-essentialist perspective on religion and ethnicity -- Epilogue: towards a sociology of Jewish religious knowledge.
Includes bibliographical references and indexes.
Master record variable field(s) change: 650
Keywords: Koigen, David; Koigen, David; Koigen, David; Religion and sociology; Jewish philosophy; Judaism -- Philosophy; Judaism -- Social aspects; SOCIAL SCIENCE -- Jewish Studies; Jewish philosophy; Judaism -- Philosophy; Judaism -- Social aspects; Religion and sociology; Electronic books; Electronic books